Bait Suci: Kemegahan Versus Penderitaan: Sebuah Tafsir Ulang atas Pembangunan Bait Suci Salomo Menurut 1 Raja-raja 5:1-18 - Agustina Raplina Samosir (Asosiasi Teolog Indonesia, 2018)
Construction for Solomon's Temple entailed forced labor. This is evinced, first, by several terms connoting forced labor, such as mas, sēbel, and ‘ebed, which are used in the text to describe the Temple project. Widely attested during the reigns of David and Solomon, terms such as these denote just how royal projects were carried out. A second piece of evidence concerns the outbreak of civil unrest during Solomon's day over the issue of forced labor in Israel. As such, the Temple's very construction bears enormous human cost, just as the splendor of that Temple is directly proportionate to the suffering of both denizens and working class. Here the author analyzes the Temple-construction process of Solomon's era, showcasing one example of the “human pyramid” that demands consideration amid a proliferation of interpretative work to be done in the present time.